2010
DOI: 10.1007/s13233-010-0307-5
|View full text |Cite
|
Sign up to set email alerts
|

New efficient polyelectrolyte containing zwitterionic sulfobetaine salt for the high sensitive resistive humidity sensor

Abstract: New sulfobetaine zwitterion-containing copolymers were prepared by the copolymerization of [2-[(methacryloyloxy)ethyl]dimethyl] propyl ammonium bromide (MEPAB)/N,N-dimethyl-N-methacryloxyethyl-N-(3-sulfopropyl) ammonium (DMMSA) for a humidity-sensitive polyelectrolyte. The poly(MEPAB-co-DMMSA)s with a composition of 10/0, 8/2, 6/4, 4/6, 3/7, 2/8 and 0/10 were used to prepare resistive-type humidity sensors. The electrical properties of poly(MEPAB-co-DMMSA) with different amounts of MEPAB and DMMSA were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Zwitterionic betaine polymers having both anions and cations in one repeating unit have high moisturizing properties due to their structural specificity and have been used in cosmetics and the like for a long time. Recently, these polymers have been found to have high biocompatibility because they have a structure similar to that of the lipids that make up the cells ,, and are applied to biomedical materials , and biosensors. , Furthermore, research is being conducted on energy materials to stabilize the interface. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zwitterionic betaine polymers having both anions and cations in one repeating unit have high moisturizing properties due to their structural specificity and have been used in cosmetics and the like for a long time. Recently, these polymers have been found to have high biocompatibility because they have a structure similar to that of the lipids that make up the cells ,, and are applied to biomedical materials , and biosensors. , Furthermore, research is being conducted on energy materials to stabilize the interface. …”
Section: Introductionmentioning
confidence: 99%
“…1−5 Recently, these polymers have been found to have high biocompatibility because they have a structure similar to that of the lipids that make up the cells 3,6,7 and are applied to biomedical materials 8,9 and biosensors. 10,11 Furthermore, research is being conducted on energy materials to stabilize the interface. 12−14 Betaine polymers are neutral in an aqueous solution, and the solubility changes depending on the concentration of the salt and the ionic species of the added salt.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DMAPS is able to copolymerize with various monomers [21][22][23][24][25]. McCormick et al [11,26,27] have synthesized a series of sulfobetaine (co)polymers by conventional freeradical techniques and found that the copolymers with 25 mol% or less of zwitterionic comonomer were soluble in deionized water and displayed a tendency to intermolecularly associate.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In general, humidity-sensitive characteristics are dependent upon the chemical structures of the polyelectrolyte humid membrane. [21][22][23][24][25][26] Their ionic moieties, such as cationic, anionic, and amphoteric, and their counter ions were directly related to sensitivity. 2,7,[27][28][29][30][31][32][33][34] In addition, the thickness of the humid membrane closely affects the humidity sensitivities, such as hysteresis and response time or recovery time.…”
Section: Introductionmentioning
confidence: 99%